Kategori Features dalam Pemberitaan Tatkala.co - Wiratama, I Wayan Agus (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2024)
The mass media or what is called journalistic media is one of the aspects that has received very large influence because of the development of electronic media. It is because the news can be disseminated very easily. This makes journalists race to modify the writing format so that it can be more attractive to readers. One of the new journalism variants chosen by journalists is feature. Journalistic article writing that uses feature writing types can be found on the electronic mass media website Tatkala.co. Unlike straight news content which emphasizes the 5W+1H elements with the inverted pyramid rule, features emphasize the